Peranan Permainan Tradisional Dalam Meningkatkan Kontrol Diri Anak Usia 6-8 Tahun - Nastiti Murdaningrum; Gregorius Ari Nugrahanta (Jurnal Gentala Pendidikan Dasar, 2021)
The purpose of this research was to develop a manual for traditional games in order to develop self-regulation character of children aged 6-8 years. The method used in this research was Research and Development (R&D). The results showed that a manual traditional games to develop self-regulation characters of children aged 6-8 years was developed based on ADDIE steps, the steps was Analyze, Design, Develop, Implement, and Evaluate. The quality of the manual for tarditional games showed the mean of “3,88” which was included in “Generally excellent” category with a recommendation "No Need for Revision". The implementation of manual for traditional games affected the self-regulation character of children aged 6-8 years. The significance test result showed t(5) = 4,804; p = 0,005 (p<0,05). The magnitude of the effect was r = 0,90 which was categorized as a “Huge impact” or equal to 82,20%. It meant that manual for traditional games could explain 82,20% play a role in developing self-regulation character of children aged 6-8 years. The level of effectiveness was showed by an N-gain score of 64,806% which was included in "Medium" category.